Surface micromachining of a micro electromechanical inertial transducer based on commercially available Floating Gate Transistor technology (Superficies y Vacío, 2018)
This work presents the results of different surface micromachining processes done on a chip from On Semiconductor 0.5 µm commercially available CMOS technology. The intended objective is to fabricate a MEMS inertial transducer in a monolithic substrate, as the electronics for signal processing are based on a Floating Gate MOS transistor, fully integrated in the electromechanical structure. According to the available layers and design rules from the foundry, an inertial sensor chip was designed and fabricated, except the last post–processing step, i.e., the removal of the sacrificial layer and thus releasing the inertial structure based on a surface micromachining process, allowing the completed device to behave as designed.